Bioinformatics in Cancer and Cancer Therapy - Gordon, Gavin J.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2009)
Bioinformatics can be loosely defined as the collection, classification, storage, and analysis of biochemical and biological information using computers and mathematical algorithms. Bioinformatics represents a marriage of biology, medicine, computer science, physics, and mathematics; fields of study that have historically existed as mutually exclusive disciplines. Edited by Gavin Gordon, Bioinformatics in Cancer and Cancer Therapy, edited by Gavin Gordon, provides an historical and technical perspective on the analytical techniques, methodologies, and platforms used in bioinformatics experiments in order to show how a bioinformatics approach has been used to characterize various cancer-related processes, and to demonstrate how a bioinformatics approach is being used to bridge basic science and the clinical arena to positively impact patient care and management.
The Emergence of Bioinformatics: Historical Perspective, Quick Overview and Future Trends -- The Statistical Design and Interpretation of Microarray Experiments -- Whole-Genome Analysis of Cancer -- Bioinformatics Approaches to the Analysis of the Transcriptome of Animal Models of Cancer -- Significance of Aberrant Expression of MicroRNAs in Cancer Cells -- Proteomic Methods in Cancer Research -- Comprehensive Genomic Profiling for Biomarker Discovery for Cancer Detection, Diagnostics and Prognostics -- Gene Expression Profiling of the Leukemias: Oncogenesis, Drug Responsiveness, and Prediction of Clinical Outcome -- Personalized Medicine in the Clinical Management of Colorectal Cancer -- Gene Alterations in Human Cancers.
Keywords: Medicine; Cancer research; Bioinformatics; Biomedicine; Cancer Research; Bioinformatics; Electronic books